Tinjauan Sistematik Pada Perancangan Sistem Kerja Di Industri Manufaktur Indonesia - Sofani, Irgi; Tanjung, Yully Wulandari; Kurnia, Hibarkah; Ningrum, Ines Pramestia; Saputro, Rian Ngesti (Journal of Industrial and Engineering System, 2022)
The manufacturing industry is a group whose main activities are to produce and process raw or semifinished materials into goods that are ready for use. Analysis of the application of work systems is very important to apply before carrying out mass production. The principles used must lead to the expected ergonomics and productivity. This study aims to identify and analyze related to the design of work systems in the manufacturing industry in Indonesia. This research method was carried out starting from the collection of articles, processing, and analysis of these articles using an analytical system. The data sources used are articles in the 2012-2022 timeframe. The results of this study found that the most published years of research were 2018 and 2022 with 5 articles each. Based on the industry, the most frequently found was the type of industry engaged in the construction sector, with 10 articles. The contribution of this research is to provide convenience for other researchers as a reference in compiling articles on work systems in the manufacturing industry.